A Quality Financial Report: A Conceptual Analysis - Hong Nhung Dao Thi; Hanh Dao Thi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
Following the loss of assets due to distortion of facts in financial reports, there is a need for ongoing study into what defines a quality financial report. A high-quality financial report should be able to achieve its primary goal of delivering useful information for economic decision-making (International Accounting Standard Board Framework). Following that, a conceptual framework for a high-quality financial report is presented. As a result, the purpose of this article is to describe the idea of a quality financial report by identifying the financial report's qualities, antecedents, and results. The financial report should include both basic and improving qualitative features in order to be useful (International Accounting Standard Board Framework). The mechanical display of the report is then added as another characteristic. The criteria taken into account here include readability, legibility, and report length. The conceptual framework will assist financial report preparers on what constitutes a great financial report, allowing them to enhance their reporting. It will also assist financial report users in assessing the quality of financial reports before using them for decision making. If this structure for a quality financial report is used, the number of financial statements scandals may be reduced, restoring investor confidence in the financial report.